The Building Information Modeling (BIM)-Based System Framework to Implement Circular Economy in Construction Waste Management - Tantri N. Handayani; Kartika Nur Rahma Putri; Nurul Alvia Istiqomah; Veerasak Likhitruangsilp (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2021)
The tremendous quantity of waste produced from construction and demolition is a major cause of environmental degradation. This quantity tends to increase due to the rapid growth of building development and renovation. Meanwhile, construction waste management is a complex and costly process due to the fact that it requires different kinds of resources such as money, land, and technology. It is often ignored by all project participants even though it is an essential element of construction project management. However, it has been discovered that modern construction waste management is structured based on the concept of circular economy which focuses on eliminating construction waste and maximizing the value of materials. Therefore, this research proposes an innovative framework to implement the circular economy using building information modeling (BIM) in order to improve the construction waste management process. This involved a thorough review of past literature to identify the implementation of the concept of circular economy, waste management, and the application of BIM, also the research gaps observed were used to develop the functionality of the proposed framework. The five functionalities include (1) visualization and data integration, (2) direct construction waste quantity take-off, (3) BIM-based sorting system and selection of appropriate disposal parties, (4) estimating cost and schedule of waste disposal, and (5) simulation and monitoring report. This BIM system was designed to analyze material waste, quantity, disposal time, and waste treatment based on project conditions, material quantities, and schedule. It can also be used to plan and monitor the construction waste process, thereby making it possible to avoid the disruption of productivity and project time usually caused by unplanned waste management activities. Moreover, the proposed on-site sorting system also has the ability to facilitate the adoption of the circular economy concept during the construction phase.